2010
DOI: 10.1016/j.ccr.2010.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Epigenetic Modulation by Cancer Amplicon Genes

Abstract: Chromosome band 9p24 is frequently amplified in primary mediastinal B-cell lymphoma (PMBL) and Hodgkin lymphoma (HL). To identify oncogenes in this amplicon, we screened an RNA interference library targeting amplicon genes and thereby identified JAK2 and the histone demethylase JMJD2C as essential genes in these lymphomas. Inhibition of JAK2 and JMJD2C cooperated in killing these lymphomas by decreasing tyrosine 41 phosphorylation and increasing lysine 9 trimethylation of histone H3, promoting heterochromatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
252
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(263 citation statements)
references
References 52 publications
9
252
1
1
Order By: Relevance
“…Our results demonstrate that FXR1 is a critical member of this large amplicon (176 genes included between 3q26-29) and contributes to the pathogenesis of lung cancer. The single gene driver theory has been challenged by recent studies (26,27), supporting that in fact multiple oncogenes work in concert to drive the cancer, sometime as a driver, sometime a passenger gene. Genomic amplifications happen in different size (Mb) and intensity (copy number between 4 and 25).…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that FXR1 is a critical member of this large amplicon (176 genes included between 3q26-29) and contributes to the pathogenesis of lung cancer. The single gene driver theory has been challenged by recent studies (26,27), supporting that in fact multiple oncogenes work in concert to drive the cancer, sometime as a driver, sometime a passenger gene. Genomic amplifications happen in different size (Mb) and intensity (copy number between 4 and 25).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have performed large scale, lossof-function short hairpin RNA (shRNA) screens to identify essential cancer genes and recently reported PAX8 and ID4 as ovarian cancer dependencies (4,5). In other cancer types, both genome-wide and targeted loss-of-function studies were used to identify novel tumor suppressors in hepatocellular carcinoma (6) and epigenetic regulators in lymphomas (7). In addition, gain-offunction, cDNA-based approaches have uncovered novel driver roles for IKBKE (8) and PAK1 (9) in breast cancer, ERBB3 in endometrial cancer (10), and FGF19 in hepatocellular cancer (11).…”
mentioning
confidence: 99%
“…The activation of this pathway in ABC tumors seems to occur through BCR signaling with acquired activating mutations in elements of this pathway including CD79a, CARD11, and MYD88 and inactivating mutations of the NFkB inhibitor A20. 29,31 The clinical, pathological, and biological features of these two types of molecular DLBCL are different, supporting the idea that they may correspond to different entities (reviewed by J Said in this course). 41,42 Other expression profiling studies have identified alternative subgroups of DLBCL characterized by expression signatures related to potential pathogenetic mechanisms.…”
Section: Characterization Of Known Entities and Recognition Of New Camentioning
confidence: 66%
“…The simultaneous amplification and overexpression of these genes has an additive effect modulating the expression of several genes including MYC. 31 Interestingly, these tumors also have deletions in 16p13 associated with inactivating mutations of SOCS1, a negative regulator of JAK2. 32 SOCS1 inactivation by biallelic mutations or mutations and deletions promotes the activity of JAK2.…”
Section: Platformsmentioning
confidence: 99%